Increasing Physical Fitness in Gender in Wetland Areas Negara Hulu Sungai Selatan District - Abd Hamid; Muhammad Mulhim; M. Rasidy; Budiannor (UNIB Press, 2023)
The purpose of this study was to determine the increase in physical fitness for gender in the wetland area of Negara Hulu Sungai Selatan District. The method used in this study is the pre-experimental method. The purpose of the pre-experiment is to obtain information that is an approximation of the information that can be obtained by the actual experiment in circumstances where it is not possible to control and manipulate all the relevant variables. The design in this study uses The One Group Pretest-Posttest design, which means that a group of subjects is subjected to treatment for a certain period of time, while measurements are made before and after treatment is given and the effect of treatment is measured from the difference between the initial measurement (O1) and the final measurement (O2). The population in this study were women in the wetlands of Negara District, while the sample size was 35 people. The results of the study showed that there was an increase in physical fitness in women in the wetlands of Negara Hulu Sungai Selatan District. The benefits of physical fitness are currently very well recognized by the community, as evidenced by the development of fitness centers and sports activities that are widely held, all of which stem from the pursuit of physical fitness.